Tracing Text Types in Biblical Hebrew - Peursen, Willem Th. van (Vetus Testamentum, 2020)
Weinrich's monograph Tempus: besprochene und erzählte Welt (1964) had a tremendous influence on the study of Biblical Hebrew. Studies by Schneider, Talstra and Niccacci and others are strongly influenced by Weinrich. In the ETCBC database of the Hebrew Bible, initiated by Eep Talstra in the 1970s, some of Weinrich's insights have been integrated. Amidst hundreds of studies in general linguistics, why was it precisely this book that had such a great impact? How should we evaluate this impact? Are Weinrich's insights still useful or have they become outdated? In this article we describe the introduction of Weinrich's insights into Biblical studies and some developments that have taken place since then, both in general linguistics and in Biblical studies. We further describe and evaluate the classification of Biblical Hebrew text types which developed from these insights